Determination of wild elephant movements in Gua Musang, Kelantan by using GIS. - Nur Hidayah Abu Kasim (2012)
One young bull Asian elephant was fitted with satellite transmitters and subsequently the satellite collar was used to determine the home range sizes and behaviour of elephant, as well as human and ecological factors that affected the home range size on highly fragmented forest lanscape in Gua Musang,Kelantan. The home range sizes were estimated by using Minimun Convex Polygon (MCP) for four months from 25ͭͪ March 2011 until 20ͭͪ June 2011. The total home range size for four months was 9482664m², Among months,the home range size in March WAS 7837607.5m², in April was 5199931.5m², in May was 5528927m², and June was 6303860m². The mean daily movement rate was 94.57m per day and total movement distance for four months was 88513m. Kampung Pasir Tadoh was inside the home range of elephant whereas Kampung Machan was above 500m away from the home range. Elephant was found on the railway and no died of train-induced injuries. The relationship between elephant movements and monthly rainfall, elevation, spedd of movement and temperature were examined by using Geographic Information System (GIS). There was no correlation between average monthly home range sizes of elephant with the raifall precipitation. However, there was relatioship between average monthly home range sizes of elephant with elevation of the locations. Types of land uses had effected on elephant movement where elephant occurred predominately in rubber estate due to consistency of food supply and water availability. High human development surrounding the home range probably affects the home range size such as railroads and human settlements. The remaining forested areas in the home range need protection from expanding plantations and human developments.